PERAN ORANG TUA DALAM MENUNJANG HASIL BELAJAR ANAK (STUDI KASUS ANAK KELAS XI IPS SMA MUJAHIDIN PONTIANAK) - Wirdani Y, Utami; Sulistyarini, Sulistyarini; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research "The Role of Parents in Supporting Children?s Learning Outcomes (A Case Study of a Class XI IPS Mujahidin High School Pontianak". This study aims to find out the general problems in this study, namely "What is the role of parents in supporting children?s learning outcomes". With the sub-problems: (1) How is the role of parents as motivators in supporting children?s learning outcomes? (2) How is the role of parents as facilitators in supporting children?s learning outcomes?(3) How is the role of parents as mediators in supporting children?s learning outcomes? The form of research used in this study is qualitative research with descriptive research methods. Data collection techniques used observation, interview and documentation techniques. The results of this study are that the the role of parents in supporting children's learning outcomes as motivators, facilitators, and mediators can be concluded that it has been implemented well, although there are some indicators that are still not maximal in its application. Keywords:  Role, Parents, Learning Outcomes, Senior High School